REQUIREMENTS FOR ECONOMIC DIVERSIFICATION IN IRAQ: AN ANALYSIS OF THE STATUS OF NON-OIL SECTORS AND THEIR DEVELOPMENT PROSPECTS - Hassan Abdullah Ahmed Al-Salihi; Tariq Abbas Jassim Al-Hatemi (Antis Publisher, 2026)
Objective: The purpose of this study is to describe the current situation of economic diversification in Iraq and explore the role of non-oil sectors in economic activity, in addition to identifying the main needs for developing the role of non-oil sectors to achieve sustainable economic growth in the years 2020-2025. Method: In this study, a descriptive analytical method is used to analyze the contribution of economic sectors to Gross Domestic Product (GDP), the export structure, the public revenues structure, and public investment expenditure structure. These indicators are used to evaluate the state of economic diversification and the key challenges that pose obstacles to economic diversification. Results: The results demonstrate that the structure of the Iraqi economy, despite the relative improvement in some non-oil sectors in the study period, remained dominated by the oil sector. The results further indicate that the limited contribution of non-oil exports and public revenues, together with the inefficient allocation of investments, continue to constitute major obstacles to achieving effective economic diversification. Novelty: The study concludes that the success of economic diversification programs requires the development of the agricultural, industrial, and service sectors, the improvement of the investment environment, the strengthening of the private sector's role, and the implementation of financial and institutional reforms that support sustainable economic development.